Feasibility test of STEM at home prototype kit as science project-based learning media for Junior High School students - Zulirfan Zulirfan; Yennita Yennita (Jurnal Penelitian Pendidikan IPA, 2022)
To promote the application of the STEM approach in science learning, it is necessary to provide cheap, easy-to-obtain, and effective STEM project support materials. In addition, science teachers should try to plan and implement STEM in their teaching, even for simple projects. To overcome the problem of the length of time on projects in science teaching, we propose "STEM at Home", a term that means that STEM projects are carried out by students at home under the supervision of parents or families. In order for this home project-based learning to be effective, we have prepared a STEM at Home Kit and Worksheet for Junior High Schools students. We chose the topic Simple. The STEM at Home Kit and Worksheet that have been developed, have received expert approval as learning media that are suitable for use. One-to-one evaluation with 3 participants, and a small group evaluation with 14 participants, were carried out to obtain feedback on students’ difficulties in using the product, their perceptions of the product, and their perceptions of the potential impact produced by the instructional product. The results of this evaluation showed that the STEM at Home Project Kit and Worksheet are valid and practically used in science learning, especially on the topic of Simple Machine